Cytological Distribution of the Products of Oxidative Assimilation in Pseudomonas aeruginosa - Tomlinson, Geraldine A. (1965)
Tomlinson, Geraldine A. (University of British Columbia, Vancouver, B.C., Canada), and J. J. R. Campbell. Cytological distribution of the products of oxidative assimilation in Pseudomonas aeruginosa. J. Bacteriol. 90:599–603. 1965.—Washed-cell suspensions of Pseudomonas aeruginosa incorporated C(14) largely into the membrane fractions and cytoplasm during oxidative assimilation of uniformly labeled glucose. The ribonucleic acid (RNA) associated with the membranes and the cytoplasm had very high specific activity in contrast to that of the ribosomes. The protein of each fraction comprised the major portion of the radioactivity of that cytological fraction. The proteins of the cytoplasm constituted the predominant product of assimilation. The low level of activity in the ribosomal RNA and protein suggests that oxidative assimilation is not the replenishment of endogenous reserves. The ribosomal fraction, which contained 19.6% of the protein and 65% of the RNA of the extract, incorporated only 2 to 3% of the radioactivity. In contrast, the membrane fraction contained 15.3% of the protein and 6.6% of the RNA, but incorporated 13 to 14% of the radioactivity.